Recreational fishers' perceptions of climate change. (1st October 2021) - Ryan, Karina L; Shaw, Jenny; Tracey, Sean R; Lyle, Jeremy M
Abstract: Shifts in marine species distributions associated with climate change occur across large spatial areas and long time periods. Marine recreational fishing occurs in most countries with many participants interacting regularly with the environment, yet there have been few studies on the views of recreational fishers towards climate change. This study aims to assess perceptions of climate change for a boat-based recreational fishery in Western Australia, where fishing occurs across a wide latitudinal range, from tropical to temperate waters. Perceptions of climate change were assessed by fisher demographics and fishing behaviour. One in two respondents noticed changes in species types and distributions, with metropolitan residents and avid fishers more likely to notice these changes. Two out of three respondents considered climate change is occurring, recognition of which was higher amongst metropolitan residents, females, and younger respondents. Males and older respondents, on the other hand considered themselves to have more knowledge of climate change science. This study provides a baseline to assist in informing policy changes that might be required to address the impacts of climate change. Studies of this kind can also build support for citizen science programs to enhance data collection across the spatial and temporal time scales required to observe climate change.